2013
DOI: 10.1111/jjns.12008
|View full text |Cite
|
Sign up to set email alerts
|

Educational needs concerning disaster preparedness and response: A comparison of undergraduate nursing students from Istanbul, Turkey, and Miyazaki, Japan

Abstract: Nursing students in both cities seem more likely to participate in disaster preparedness and response courses/lectures. The present study also addresses the need to incorporate mass casualty care and disaster management skills into undergraduate curricula. Core contents for nursing curricula in both cities need to be continued. Outcome competencies must be identified and validated through further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Moreover, student gender and academic year showed significant differences with respect to readiness to practice. A study in Turkey among nursing students found that respondents seemed more likely to participate in disaster preparedness and recommended including disaster management skills and mass casualty care into the undergraduate curricula [50]. Kaiser et al found that more than four-fifths of medical students reported a willingness to respond to a natural disaster, pandemic influenza, and a radiological event [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, student gender and academic year showed significant differences with respect to readiness to practice. A study in Turkey among nursing students found that respondents seemed more likely to participate in disaster preparedness and recommended including disaster management skills and mass casualty care into the undergraduate curricula [50]. Kaiser et al found that more than four-fifths of medical students reported a willingness to respond to a natural disaster, pandemic influenza, and a radiological event [41].…”
Section: Discussionmentioning
confidence: 99%
“…Academic institutions can contribute leadership and resources to societal disaster preparedness [53]. Several studies strongly recommended that continuous and consistent disaster knowledge, skills, and preparedness content be included in college curricula [50][51][52][53][54][55][56].…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…In those nursing programs identified as offering disaster-nursing education, the teaching methods were predominantly didactic and passive. Investigation of Australian, Turkey, and Asian nursing colleges [13,32,33] also suggested similar challenges.…”
Section: The Importance Of Disaster Nursing Education In Undergraduatesmentioning
confidence: 96%
“…Core contents for nursing curricula in both cities need to be continued. Outcome competencies must be identified and validated through further research [21] Most nurses receive little, if any, disaster preparedness education in nursing school. A 2003 survey of 2013 schools of nursing (348 responding) revealed that only 53% offered content in disaster preparedness, and a mean of 4 hours was devoted to this content.…”
Section: Discussionmentioning
confidence: 99%